A silver-carbon negative electrode material for solid-state lithium battery and a preparation method thereof

By using lithiated silver carbon negative electrode materials in solid-state lithium batteries, the safety hazards and low energy density caused by metal lithium negative electrode materials are solved, higher safety performance and energy density are achieved, and the commercial application of solid-state lithium batteries is promoted.

CN115172692BActive Publication Date: 2025-03-18成都佰思格科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210813343.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-11
Publication Date
2025-03-18
Estimated Expiration
2042-07-11

AI Technical Summary

Technical Problem

In the prior art, metal lithium anode materials limit the application of solid-state lithium batteries, resulting in safety hazards and low energy density problems.

Method used

A silver carbon negative electrode material for solid lithium batteries and its preparation method are adopted. Nanosilver is generated in situ in the carbon source by silver nitrate, silver fluoride, silver perchlorate or silver acetate as silver sources to form a silver carbon negative electrode material without lithiation, and promote uniform deposition of metal lithium.

Benefits of technology

It improves the safety performance and energy density of solid-state lithium batteries, simplifies production processes, reduces production costs, and promotes the commercial application of solid-state lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115172692B_ABST
    Figure CN115172692B_ABST
Patent Text Reader

Abstract

The present invention provides a silver-carbon negative electrode material for solid-state lithium batteries and a preparation method thereof, and relates to the technical field of energy storage materials. The preparation method comprises the following steps: adding a carbon source, poloxamer and a silver source to deionized water, stirring at room temperature to obtain a first dispersion; adding potassium hydroxide to the first dispersion, stirring at room temperature for 1-5 hours, heating to 90°C, stirring for 12-48 hours, and obtaining a second dispersion; adding a reducing agent to the second dispersion, stirring at room temperature for reaction, and drying to obtain a silver-carbon precursor; subjecting the silver-carbon precursor to high-temperature treatment under inert gas protection to obtain a silver-carbon negative electrode material for solid-state lithium batteries. The preparation method of the silver-carbon negative electrode material for solid-state lithium batteries provided by the present invention introduces silver through a silver source to obtain a non-lithiated silver-carbon negative electrode material, promotes uniform deposition of metallic lithium during the discharge process of the solid-state lithium battery, avoids the growth of lithium dendrites on one side of the metallic lithium, reduces safety hazards, and promotes the commercial application of solid-state lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage materials, and in particular to a silver-carbon negative electrode material for a solid-state lithium battery and a preparation method thereof. Background Art

[0002] Since traditional lithium-ion batteries use flammable and explosive organic carbonate electrolytes as organic electrolytes, they are prone to battery explosions due to electrolyte leakage during use, and are not very safe. Currently, one way to improve battery safety is to use solid-state lithium batteries to replace traditional lithium-ion batteries.

[0003] Existing solid-state lithium batteries usually introduce metallic lithium into the negative electrode material to obtain a high energy density battery negative electrode; although metallic lithium has a high theoretical specific capacity and low electrochemical potential, lithium easily reacts with the electrolyte in the solid-state lithium battery, resulting in reduced battery coulombic efficiency, shortened cycle life, and even serious safety accidents such as combustion and explosion. The fundamental reason for the performance impact and safety accidents is the uneven deposition of metallic lithium, which leads to the growth of lithium dendrites, which pierce the diaphragm, causing the battery to short-circuit and cause safety problems.

[0004] At present, the main methods to inhibit the growth of lithium dendrites are: (1) constructing an artificial SEI film on the surface of lithium metal; (2) regulating the structure of the lithium metal negative electrode, for example, adopting mold rolling, composite with three-dimensional skeleton, etc. to achieve the regulation of the deposition active position on the surface of lithium metal, thereby improving the cycle stability of lithium metal; (3) improving the composition of the electrolyte, for example, adding inorganic fillers such as SiO2 and LLZO to the electrolyte, regulating the distribution and transmission of anions and lithium ions, thereby improving the deposition behavior of lithium metal; at the same time, improving the mechanical strength of the electrolyte to inhibit the penetration of lithium dendrites.

[0005] However, due to the soft texture of metallic lithium, its use in solid-state lithium batteries requires hot pressing, which increases the complexity and cost of production and limits the commercial application of solid-state lithium batteries. At the same time, excessive use of metallic lithium in solid-state lithium batteries will reduce the energy density of the battery and hinder the commercial application of the battery.

[0006] In view of this, seeking a non-lithium negative electrode material to replace metallic lithium for solid-state lithium batteries is an effective way to achieve the commercial application of high-energy-density solid-state lithium batteries. Summary of the invention

[0007] The technical problem to be solved by the present invention is: in order to solve the problem that metal lithium negative electrode materials limit the application of solid-state lithium batteries in the prior art, the present invention provides a silver-carbon negative electrode material for a solid-state lithium battery and a preparation method thereof. In the preparation process, silver nitrate, silver fluoride, silver perchlorate or silver acetate is used as a silver source to obtain a lithiation-free silver-carbon negative electrode material that can promote uniform deposition of metal lithium, improve the performance of solid-state lithium batteries, promote the commercial application of solid-state lithium batteries, and solve the problem that metal lithium negative electrode materials limit the application of solid-state lithium batteries in the prior art.

[0008] The technical solution adopted by the present invention to solve its technical problem is:

[0009] A method for preparing a silver-carbon negative electrode material for a solid-state lithium battery comprises the following steps:

[0010] S1: adding a carbon source, poloxamer and a silver source into deionized water and stirring at room temperature to obtain a first dispersion;

[0011] S2: adding potassium hydroxide to the first dispersion, stirring at room temperature for 1-5 hours, heating to 90° C., stirring for 12-48 hours, to obtain a second dispersion;

[0012] S3: adding a reducing agent to the second dispersion, stirring at room temperature for reaction, and drying to obtain a silver-carbon precursor;

[0013] S4: subjecting the silver-carbon precursor to high-temperature treatment at 700-900° C. under the protection of an inert gas to obtain a silver-carbon negative electrode material for a solid-state lithium battery.

[0014] Optionally, the carbon source is sulfonated asphalt.

[0015] Optionally, the silver source is selected from at least one of silver nitrate, silver fluoride, silver perchlorate and silver acetate.

[0016] Optionally, the base is selected from at least one of potassium hydroxide and sodium hydroxide.

[0017] Optionally, the reducing agent is an aqueous solution of hydroxylamine.

[0018] Optionally, the concentration of the hydroxylamine aqueous solution is 5 mM.

[0019] Optionally, the mass ratio of the alkali, the sulfonated asphalt, the poloxamer and the silver source is 40:80:80:1-4.

[0020] Optionally, the temperature rising procedure of the high temperature treatment in step S4 includes: heating to 700-900° C. at a heating rate of 10° C. / min, maintaining for 1 hour, and then naturally cooling to room temperature.

[0021] Another object of the present invention is to provide a silver-carbon negative electrode material for a solid-state lithium battery, which is prepared by the preparation method of the silver-carbon negative electrode material for a solid-state lithium battery as described above.

[0022] The beneficial effects of the present invention are:

[0023] The present invention provides a method for preparing a silver-carbon negative electrode material for a solid-state lithium battery. The method comprises the following steps: firstly fully mixing a carbon source and a silver source, and then performing a reduction reaction on the silver source, thereby generating nanosilver in situ in the carbon source, so that the nanosilver can be evenly distributed in the carbon source, thereby improving the structural stability and performance uniformity of the silver-carbon negative electrode material for a solid-state lithium battery. The negative electrode material prepared by the method introduces silver through the silver source to obtain a non-lithiated silver-carbon negative electrode material. The silver in the negative electrode material can reduce the nucleation energy of lithium, thereby promoting the uniform deposition of metallic lithium during the discharge process of the solid-state lithium battery, avoiding the growth of lithium dendrites on one side of the metallic lithium, reducing potential safety hazards, and improving the safety of the solid-state lithium battery. energy; and, the carbon material introduced into the negative electrode material through the carbon source can, on the one hand, promote the uniform dispersion of silver nanoparticles and prevent silver from agglomerating during the charging and discharging process; on the other hand, it can serve as a three-dimensional main body for lithium metal deposition, further improving the uniformity of metal lithium deposition, thereby further reducing safety hazards; in addition, since the negative electrode material does not contain lithium, when used in solid-state lithium batteries, no hot pressing is required, which is conducive to simplifying the production process and improving production efficiency; at the same time, it helps to reduce the metal lithium used in solid-state lithium batteries, thereby helping to improve the energy density of the battery, thereby helping to expand the scope of use of solid-state lithium batteries and promote the commercial application of solid-state lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0025] Figure 1 is a scanning electron microscope image of the silver-carbon negative electrode material prepared in Example 1 of the present invention;

[0026] Figure 2 is a transmission electron microscope image of the silver-carbon negative electrode material prepared in Example 1 of the present invention;

[0027] Figure 3 is an X-ray diffraction pattern of the silver-carbon negative electrode material prepared in Example 1 of the present invention;

[0028] Figure 4 is a charge and discharge curve diagram of the solid-state full battery in Example 1 of the present invention;

[0029] Figure 5 is a cycle performance diagram of the solid-state full battery in Example 1 of the present invention;

[0030] Figure 6 This is a cycle performance diagram of the solid-state full battery in Example 2 of the present invention. DETAILED DESCRIPTION

[0031] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0032] In order to seek a non-lithiated negative electrode material to replace metallic lithium for solid-state lithium batteries, the present invention provides a method for preparing a silver-carbon negative electrode material for solid-state lithium batteries, the preparation method comprising the following steps:

[0033] S1: adding a carbon source, poloxamer and a silver source to deionized water, stirring at room temperature, to obtain a first dispersion; wherein poloxamer, as a surfactant, can promote better combination of the hydrophobic carbon source and the hydrophilic silver source;

[0034] S2: adding alkali to the first dispersion, stirring at room temperature for 1-5 hours, heating to 90°C, stirring for 12-48 hours, to obtain a second dispersion;

[0035] S3: adding a reducing agent to the second dispersion, stirring at room temperature for reaction, and drying to obtain a silver-carbon precursor;

[0036] S4: The silver-carbon precursor is subjected to high-temperature treatment at 700-900° C. under the protection of an inert gas to obtain a silver-carbon negative electrode material for a solid-state lithium battery.

[0037] The present invention provides a method for preparing a silver-carbon negative electrode material for a solid-state lithium battery. The method comprises the following steps: firstly fully mixing a carbon source and a silver source, and then performing a reduction reaction on the silver source, thereby generating nanosilver in situ in the carbon source, so that the nanosilver can be evenly distributed in the carbon source, thereby improving the structural stability and performance uniformity of the silver-carbon negative electrode material for a solid-state lithium battery. The negative electrode material prepared by the method introduces silver through the silver source to obtain a non-lithiated silver-carbon negative electrode material. The silver in the negative electrode material can reduce the nucleation energy of lithium, thereby promoting the uniform deposition of metallic lithium during the discharge process of the solid-state lithium battery, avoiding the growth of lithium dendrites on one side of the metallic lithium, reducing potential safety hazards, and improving the safety of the solid-state lithium battery. energy; and, the carbon material introduced into the negative electrode material through the carbon source can, on the one hand, promote the uniform dispersion of silver nanoparticles and prevent silver from agglomerating during the charging and discharging process; on the other hand, it can serve as a three-dimensional main body for lithium metal deposition, further improving the uniformity of metal lithium deposition, thereby further reducing safety hazards; in addition, since the negative electrode material does not contain lithium, when used in solid-state lithium batteries, no hot pressing is required, which is conducive to simplifying the production process and improving production efficiency; at the same time, it helps to reduce the metal lithium used in solid-state lithium batteries, thereby helping to improve the energy density of the battery, thereby helping to expand the scope of use of solid-state lithium batteries and promote the commercial application of solid-state lithium batteries.

[0038] The preferred carbon source of the present invention is sulfonated asphalt. The advantages of sulfonated asphalt as a carbon source are as follows: 1. Compared with conventional asphalt or organic matter, sulfonated asphalt has better compatibility with water, so it can be better and more evenly combined with the silver source, and the silver is more evenly distributed in the carbon, which reduces the amount of silver source used and improves the performance of silver-carbon materials; 2. As a bulk industrial product, sulfonated asphalt has a wide source and low cost. Compared with the hydrophilic carbon sources reported in other literature, it has more mass production value.

[0039] The preferred silver source of the present invention is selected from at least one of silver nitrate, silver fluoride, silver perchlorate and silver acetate; the preferred alkali is selected from at least one of potassium hydroxide and sodium hydroxide; the sulfonated asphalt, poloxamer and the silver source are fully mixed, and then a strong base and a reducing agent are added in sequence, and after stirring and drying, a silver-carbon precursor with shallow micropores is obtained; and after further high-temperature treatment, a silver-carbon negative electrode material with shallow micropores is obtained.

[0040] Due to the small amount of strong alkali added, the degree of etching and pore formation on the carbon material during the heat treatment process is weak, and the formed pore structure is shallow, so that a silver-carbon negative electrode material with shallow micropores can be obtained; compared with the traditional highly activated, high-specific surface area activated carbon with complex pore structure, the silver-carbon negative electrode with shallow micropore structure has silver distributed in a shallower layer. During charging, lithium ions can quickly combine with silver and enter the micropores, instead of accumulating on the surface of the carbon negative electrode to form dendrites.

[0041] In order to ensure the electrochemical performance of the silver-carbon negative electrode material for solid-state lithium batteries, the preferred reducing agent in the present invention is a hydroxylamine aqueous solution, and further preferably the concentration of the hydroxylamine aqueous solution is 5 mM.

[0042] The preferred mass ratio of the alkali, sulfonated asphalt, poloxamer and silver source in the present invention is 40:80:80:1-4.

[0043] The preferred temperature raising procedure of the high temperature treatment in step S4 of the present invention includes: heating to 700-900° C. at a heating rate of 10° C. / min, maintaining for 1 hour, and then naturally cooling to room temperature.

[0044] Another object of the present invention is to provide a silver-carbon negative electrode material for a solid-state lithium battery, which is prepared by the preparation method of the silver-carbon negative electrode material for a solid-state lithium battery as described above.

[0045] The silver-carbon negative electrode material for solid-state lithium batteries provided by the present invention introduces silver through a silver source during the preparation process to obtain a non-lithiated silver-carbon negative electrode material. The silver in the negative electrode material can reduce the nucleation energy of lithium, thereby promoting the uniform deposition of metallic lithium during the discharge process of the solid-state lithium battery, avoiding the growth of lithium dendrites on one side of the metallic lithium, reducing safety hazards, and improving the safety performance of the solid-state lithium battery. In addition, the carbon material introduced into the negative electrode material through the carbon source can, on the one hand, promote the uniform dispersion of silver nanoparticles and prevent silver from agglomerating during the charge and discharge process, and on the other hand, can serve as a three-dimensional main body for lithium metal deposition, further improving the uniformity of metallic lithium deposition, thereby further reducing safety hazards. In addition, since the negative electrode material does not contain lithium, when used in a solid-state lithium battery, hot pressing is not required, which is conducive to simplifying the production process and improving production efficiency. At the same time, it helps to reduce the metallic lithium used in the solid-state lithium battery, thereby helping to improve the energy density of the battery, thereby helping to expand the scope of use of the solid-state lithium battery and promote the commercial application of the solid-state lithium battery.

[0046] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0047] Example 1

[0048] This embodiment provides a method for preparing a silver-carbon negative electrode material for a solid-state lithium battery, the preparation method comprising the following steps:

[0049] S1: Add 1 g of sulfonated asphalt, 1 g of poloxamer and 0.0125 g of silver nitrate to 200 mL of deionized water and stir at room temperature for 2 h to obtain a first dispersion;

[0050] S2: Add 0.5 g potassium hydroxide to the first dispersion, stir at room temperature for 3 h, then heat to 90° C. and stir for 20 h to obtain a second dispersion;

[0051] S3: Add hydroxylamine aqueous solution (5 mM, 7.5 μL) to the second dispersion, stir at room temperature for 4 h, and dry to obtain a silver-carbon precursor;

[0052] S4: The silver-carbon precursor is subjected to high-temperature treatment at 800°C under Ar atmosphere protection, wherein the heating program of the high-temperature treatment is: heating to 800°C at a heating rate of 10°C / min, maintaining for 2 hours, and naturally cooling to room temperature to obtain a silver-carbon negative electrode material for a solid-state lithium battery.

[0053] The silver-carbon negative electrode material prepared in this example was tested, and the test spectrum is shown in Figure 1-Figure 3 shown.

[0054] Preparation of negative electrode sheet:

[0055] The obtained silver-carbon negative electrode material was uniformly mixed with conductive carbon (Super P) and a binder (polyvinylidene fluoride) at a mass ratio of 8:1:1, and 800 μL of N-methylpyrrolidone was added. After stirring at room temperature for 6 hours, the obtained suspension was uniformly coated on a copper foil (the coating amount per square centimeter of copper foil was about 1 mg), and dried at 80°C for 10 hours; the obtained electrode sheet was cut into discs with a diameter of 12 mm using a manual slicer to obtain a negative electrode sheet.

[0056] Preparation of positive electrode sheet: lithium iron phosphate, conductive carbon (Super P) and binder (polyvinylidene fluoride) are uniformly mixed at a mass ratio of 8:1:1, and N-methylpyrrolidone is added and stirred at room temperature for 6 hours; after stirring, the resulting suspension is uniformly coated on aluminum foil (the coating amount per square centimeter of aluminum foil is about 4 mg), and air dried at 80°C for 12 hours to obtain the positive electrode sheet of the solid-state lithium metal battery.

[0057] Preparation of solid electrolyte: PEO and lithium bis(trifluoromethanesulfonyl)imide were uniformly mixed at a mass ratio of 5:2 and acetonitrile was added, and stirred at room temperature for 10 hours. After stirring, the resulting suspension was placed in a polytetrafluoroethylene mold to dry into a film; after drying, the film was taken out and cut into discs with a diameter of 20 mm to obtain a solid electrolyte.

[0058] The battery in this embodiment adopts a standard full-cell configuration, the battery shell is a CR2030 stainless steel button battery shell, and the electrolyte is a mixed solution of 1M LiPF6 dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) (volume ratio 1:1). When the full battery is assembled, the mass ratio of the positive and negative active materials is 2.3:1, and 10μL of electrolyte is added to the positive and negative electrodes close to the diaphragm. The test voltage range is 0.01~3V, and the test current is 80mAg -1 The test adopts LAND CT2001A battery test system.

[0059] See also Figure 4 , Figure 5 As shown in FIG. 1 , when the silver-carbon negative electrode material prepared in this embodiment is used, the discharge and charge specific capacities of the solid-state full battery in the first cycle are 78.2 and 94.1 mAh g -1 After 20 cycles, the reversible specific capacity reaches 92.2 mAh g -1 .

[0060] Example 2

[0061] The difference between this embodiment and embodiment 1 is that the added amount of silver nitrate is 0.025 g.

[0062] For the test process in this embodiment, please refer to the relevant content in Embodiment 1.

[0063] After testing, when the silver-carbon negative electrode material prepared in this embodiment is used, see Figure 6 As shown in Figure 2, the discharge and charge specific capacities of the solid-state lithium battery in the first cycle are 83.6 and 100.6 mAh g, respectively. -1 After 20 cycles, the reversible specific capacity reaches 98.7 mAh g -1 .

[0064] Example 3

[0065] The difference between this embodiment and embodiment 1 is that the added amount of silver nitrate is 0.0375 g.

[0066] For the test process in this embodiment, please refer to the relevant content in Embodiment 1.

[0067] The test shows that when the silver-carbon negative electrode material prepared in this embodiment is used, the discharge and charge specific capacities of the solid-state lithium battery in the first cycle are 82.8 and 99.8 mAh g -1 After 20 cycles, the reversible specific capacity reaches 94.4 mAh g -1 .

[0068] Comparative Example 1

[0069] This comparative example provides a method for preparing a silver-carbon negative electrode material for a solid-state lithium battery, the preparation method comprising the following steps:

[0070] S1: Add 1 g of sulfonated asphalt, 1 g of poloxamer, 0.5 g of potassium hydroxide and 0.0125 g of silver nitrate to 100 mL of deionized water and stir at room temperature for 2 h to obtain a first dispersion;

[0071] S2: Add hydroxylamine aqueous solution (5 mM, 7.5 μL) to the first dispersion, stir at room temperature for 4 h, and dry to obtain a second dispersion;

[0072] S3: heating the second dispersion to 90° C. and stirring for 20 h to obtain a silver-carbon precursor;

[0073] S4: The silver-carbon precursor is subjected to high-temperature treatment at 800°C under Ar atmosphere protection, wherein the heating program of the high-temperature treatment is: heating to 800°C at a heating rate of 10°C / min, maintaining for 2 hours, and naturally cooling to room temperature to obtain a silver-carbon negative electrode material.

[0074] The test process in this comparative example refers to the relevant content in Example 1.

[0075] The test shows that when the silver-carbon negative electrode material prepared in this comparative example is used, the discharge and charge specific capacities of the solid-state lithium battery in the first cycle are 47.1 and 56.6 mAh g -1After 20 cycles, the reversible specific capacity reached 42.2 mAh g -1 .

[0076] The difference between this comparative example and Example 1 is that the preparation process is replaced while the raw material composition remains unchanged; by comparing the test results of this comparative example with those of Example 1, it is found that the electrochemical performance of the silver-carbon negative electrode material prepared in this comparative example is far inferior to that of Example 1.

[0077] Comparative Example 2

[0078] This comparative example provides a method for preparing a silver-carbon negative electrode material for a solid-state lithium battery, the preparation method comprising the following steps:

[0079] S1: Add 2 g of sulfonated asphalt and 0.0125 g of silver nitrate to 200 mL of deionized water and stir at room temperature for 2 h to obtain a first dispersion;

[0080] S2: Add 1 g of potassium hydroxide to the first dispersion, stir at room temperature for 3 h, then heat to 90° C. and stir for 20 h to obtain a second dispersion;

[0081] S3: Add hydroxylamine aqueous solution (5 mM, 7.5 μL) to the second dispersion, stir at room temperature for 4 h, and dry to obtain a silver-carbon precursor;

[0082] S4: The silver-carbon precursor is subjected to high-temperature treatment at 800°C under Ar atmosphere protection, wherein the heating program of the high-temperature treatment is: heating to 800°C at a heating rate of 10°C / min, maintaining for 2 hours, and naturally cooling to room temperature to obtain a silver-carbon negative electrode material.

[0083] The test process in this comparative example refers to the relevant content in Example 1.

[0084] The test shows that when the silver-carbon negative electrode material prepared in this comparative example is used, the discharge and charge specific capacities of the solid-state lithium battery in the first cycle are 59.1 and 70.3 mAh g, respectively. -1 After 20 cycles, the reversible specific capacity reaches 58.7 mAh g -1 .

[0085] The difference between this comparative example and Example 1 is that poloxamer is not added; by comparing the test results of this comparative example with those of Example 1, it is found that the electrochemical performance of the silver-carbon negative electrode material prepared in this comparative example is far worse than that of Example 1.

[0086] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a silver-carbon negative electrode material for a solid-state lithium battery, characterized in that: The steps include: S1: adding a carbon source, poloxamer and a silver source into deionized water and stirring at room temperature to obtain a first dispersion; S2: adding a base to the first dispersion, stirring at room temperature for 1-5 hours, heating to 90° C., stirring for 12-48 hours, to obtain a second dispersion; S3: adding a reducing agent to the second dispersion, stirring at room temperature for reaction, and drying to obtain a silver-carbon precursor; S4: subjecting the silver-carbon precursor to high-temperature treatment at 700-900° C. under inert gas protection to obtain a silver-carbon negative electrode material for a solid-state lithium battery; The carbon source is sulfonated asphalt; The mass ratio of alkali, sulfonated asphalt, poloxamer and silver source is 40:80:80:1-4.

2. The method for preparing a silver-carbon negative electrode material for a solid-state lithium battery according to claim 1, characterized in that: The silver source is selected from at least one of silver nitrate, silver fluoride, silver perchlorate and silver acetate.

3. The method for preparing the silver-carbon negative electrode material for solid-state lithium battery according to claim 1, characterized in that: The alkali is selected from at least one of potassium hydroxide and sodium hydroxide.

4. The method for preparing a silver-carbon negative electrode material for a solid-state lithium battery according to claim 1, characterized in that: The reducing agent is a hydroxylamine aqueous solution.

5. The method for preparing a silver-carbon negative electrode material for a solid-state lithium battery according to claim 4, characterized in that: The concentration of the hydroxylamine aqueous solution is 5 mmol / L.

6. The method for preparing a silver-carbon negative electrode material for a solid-state lithium battery according to any one of claims 1 to 5, characterized in that: The temperature rise procedure of the high temperature treatment in step S4 includes: heating to 700-900°C at a heating rate of 10°C / min, maintaining for 1 h, and then naturally cooling to room temperature.

7. A silver-carbon negative electrode material for a solid-state lithium battery, characterized in that: The method is described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of anode material for lithium-ion power battery

    CN105161725A